1997
DOI: 10.1093/njaf/14.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife Responses to Thinning Red Pine

Abstract: Red pine is the most intensively managed conifer type in the Lake States, but its typical stand structure of a closed canopy with little understory results in poor wildlife habitat. We evaluated the effects of thinning mature red pine stands on wildlife habitat attributes and use. Red pine stands were thinned to a residual basal area of 16.1 m²/ha and 25.3 m²/ha and compared with controls (>32.1 m²/ha) in terms of understory development, small mammal use, and ungulate use. Overstory thinning resulted in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We know that native ungulates do not exist in a homogenous environment and their effects on vegetation are likely to vary across productivity gradients (Milchunas and Lauenroth 1993, Osem et al 2004, Pakeman 2004. Not only are ungulate effects likely to vary as a function of site productivity, but effects are likely to vary as a function of the ungulate species and ungulate density, which in turn may vary as a function of site productivity-with different or more ungulates in areas that are more productive (Bender et al 1997, Bauer 1990). However, little field data exist to determine whether these interdependent factors stabilize productivity across environmental gradients over the long term in shrubsteppe ecosystems.…”
Section: Future Directionsmentioning
confidence: 99%
“…We know that native ungulates do not exist in a homogenous environment and their effects on vegetation are likely to vary across productivity gradients (Milchunas and Lauenroth 1993, Osem et al 2004, Pakeman 2004. Not only are ungulate effects likely to vary as a function of site productivity, but effects are likely to vary as a function of the ungulate species and ungulate density, which in turn may vary as a function of site productivity-with different or more ungulates in areas that are more productive (Bender et al 1997, Bauer 1990). However, little field data exist to determine whether these interdependent factors stabilize productivity across environmental gradients over the long term in shrubsteppe ecosystems.…”
Section: Future Directionsmentioning
confidence: 99%
“…It has also been shown to enhance the growth rate of the remaining trees ( 29 ) and decrease their mortality rate ( 9 ). However, thinning also influences the understory organisms in forest ecosystems ( 6 , 42 , 63 ), thereby affecting the functions of the ecosystem ( 7 ).…”
mentioning
confidence: 99%
“…Thinning of red pine in Michigan resulted in strong positive responses in ungulates (deer, elk), likely due to increased forage resources and hiding cover (Bender et al 1997). Other research has identified mixed results in response of small mammal species to thinning treatments (Bender et al 1997, Converse et al 2006.…”
Section: Provision Of Wildlife Habitatmentioning
confidence: 99%
“…Thinning of red pine in Michigan resulted in strong positive responses in ungulates (deer, elk), likely due to increased forage resources and hiding cover (Bender et al 1997). Other research has identified mixed results in response of small mammal species to thinning treatments (Bender et al 1997, Converse et al 2006. Wildlife responses to thinning may decline 4 to 5 years post-thinning as the canopy closes; thus, periodic thinning may be necessary if continued wildlife use is a management priority (Bender et al 1997).…”
Section: Provision Of Wildlife Habitatmentioning
confidence: 99%